The Influence of Digital Marketing Strategies and Digital Payments on UMKM Buying Decisions in the Digital Era - Br Ginting, Stefani; Irawan, Alyarifah Hidayah; urbakti, Delta Citra Lestari S; Alifah, Rifatul; Saraswati, Dwi (Indonesian Journal Publisher, 2024)
This study aims to identify the influence of digital marketing strategies and digital payments on buyer decisions in UMKM in the digital era. With the rapid development of technology, digital marketing and payments have become crucial aspects in business activities. The research method used is a survey with 53 respondents who are UMKM buyers. Data were collected through questionnaires and analyzed using multiple linear regression techniques. The results of the study show that the Digital Marketing Strategy Variable shows a tcount of -0.076. Meanwhile, the ttable value = -1.054 so that tcount> ttable (-0.076 > -1.054) with a significance probability of (0.297 > 0.05). The Digital Payment Variable shows a tcount of 0.040. Meanwhile, the ttable value = 0.273 so that tcount > ttable (0.040 <0.273) with a significance probability of 0.786 > 0.05. The implication of this finding is that digital marketing strategies and digital payments have an influence on buyer decisions, although not significantly. This research contributes to the literature on digitalization in UMKM businesses and provides insights for UMKM actors to improve their marketing strategies and payment methods.